Terapi Non Farmakologis untuk Mengurangi Nyeri Haid pada Remaja di Tabanan - Ariyanti, Kadek Sri; Sariyani, Made Dewi; Winangsih, Rini (Jurnal Kebidanan Malakbi, 2022)
Numerous physical and psychological changes occur during adolescence. Adolescent girls' bodies undergo physiological changes as their reproductive systems grow and menstruation begins. Women who have menstruation may experience worry because it frequently results in discomfort. Menstrual discomfort could be reduced by non-pharmacological therapy, according to some experts. Approximately 96% of teenagers in Tabanan who participated in a study of various youths revealed that they had had dysmenorrhea or menstrual pain. The study attempts to characterize the non-pharmacological therapy utilized by teenagers in Bali's Tabanan Regency to lessen menstrual pain. Using random sampling, we acquired a sample of 121 young women in Tabanan Regency, aged 11 to 21. The findings revealed that using eucalyptus oil and drinking herbal teas are the most popular non-pharmacological treatments used by teenagers to lessen period pain for about 55% and 42%. Heated ginger (22%), sour turmeric (42%), and coconut water (14%) are herbal beverages that are said to have pain-relieving properties. There is a need to strengthen adolescent females' understanding of menstrual discomfort, anticipation, and management.